Percentage problems in bridging courses - Kachapova, F; Kachapov, I (Taylor and Francis, 2012)
Research on teaching high school mathematics shows that the topic of percentages often causes learning difficulties. This article describes a method of teaching percentages that the authors used in university bridging courses. In this method, the information from a word problem about percentages is presented in a two-way table. Such a table gives a logical structure to the problem and provides an algorithm for finding a simple equation for the unknown value of interest. The use of this procedure is illustrated by several examples of different levels of difficulty. The method can be applied to many types of percentage problems, so it is quite universal.
Keywords: Percentage; Proportion; Table; Bridging course; Problem-solving; Percentage increase; Percentage decrease; Profit; Bank interest